How local wisdom-based story calendar media improve patriotism character of elementary students? - Moh. Farizqo Irvan; Ali Mustadi (Jurnal Prima Edukasia, 2021)
This research aims to find out the effectiveness of local wisdom-based story calendar media in improving students’ patriotism character. The type of research is pseudo- experimental, by using a nonequivalent control group design. The population of the study is the fourth-grade students of an elementary school in Ngaliyan District, Semarang, in the even semester, the academic year 2019/2020. The subjects were determined by implementing cluster random sampling. The influence of the media on students’ patriotism was measured using n-gain and independent t-tests. The results showed that the n-gain of students’ patriotism in the experimental class I and experimental class II were higher than the control class, such as 0.37, 0.39, and 0.07 with a moderate category for experimental class and low category for control class. Independent t-test results also showed that the value (p) were 0.025 and 0.044 ≤ 0.05, so there are significant differences in student’s patriotism character between experimental dan control class. So, it can conclude that the local wisdom-based story calendar media is effective for improving students’ patriotism character in the fourth grade of elementary school.